A Facile One-Pot Hydrothermal Method to Produce SnS/Reduced Graphene Oxide and Its Application in Removal of Dyes from Aqueous Solution - Zhu, Lei; Jo, Sun-Bok; Ye, Shu; Ullah, Kefayat; Meng, Ze-Da; Oh, Won-Chun (Asian Journal of Chemistry, 2014)
In this work, we report a novel one-pot synthesis of SnS/reduced graphene oxide nanocomposites via in situ reduction of graphene oxide by Sn2+ under ethylene glycol assisted hydrothermal conditions. The morphology and structure of the obtained product were characterized by Fourier transform infrared spectroscopy, X-ray diffraction, scanning electron microscopy with energy dispersive X-ray analysis, transmission electron microscopy and UV-visible diffuse reflectance spectrophotometer. The as-synthesized graphene-SnS composite efficiently catalyzed the photodegradation of methyl orange with high concentration in aqueous solutions under visible light irradiation. Based on the high photocatalytic activity, the graphene-SnS composite can be expected to be a practical visible light photocatalyst.